Productivity of sorghum (Sorghum bicolor) as affected by legume intercropping under different fertility systems - Arya, R L; Niranjan, K P (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during rainy season of 1990, 1991 and 1992 to study productivity of sorghum [Sorghum bicolor (L.) Moench] as affected by legume intercropping under different levels of fertilizers. There were 12 treatments, involving different sources of nitrogen with and without intercrops. Applicatfon of 100% Inorganic fertilizer (60 kg N/ha + P/ha) gave significantly highest grain (1.41 tonnes/ha) and stover (16.79 tonnes/ha) yields of sorghum compared with the control. Among intercropping, the highest green-fodder yield (19.3 tonnes/ha) was obtained from sorghum + cowpea [Vigna unguiculata (L.) Walp.] with 50% inorganic fertilizers PO kg N/ha + 8.8 P/ha). The organic carbon content, available nitrogen and available potassium in the soil restored more in the plots receiving farmyard manure@ 12 tonnes/ha, followed by white popinac [Leucaena latisilliqua (L.) Gillis; syn L. leucocephalo (Lam.) deWit] leaves @6 tonnes/ha. However, the available phosphorus in soil was higherwith 100% inorganic fertilizer.